Implementasi Pelaksanaan Kegiatan Keagamaan Dalam Meningkatkan Kecerdasan Spiritual Siswa Sekolah Menengah Pertama Negeri 1 Sumberasih - Hamid, Abdul; Prasetiya, Benny; Santoso, Subhan Adi (STIT Muhammadiyah Paciran Lamongan, 2022)
This research aims to determine the religious activities carried out in SMP Negeri 1 Sumberasih. This research is a field research (Field Research) which is a qualitative research that is descriptive analytic with a pedagogical approach. The results of the study prove that the activities carried out at SMP Negeri 1 Sumberasih are based on religious activities. During the research, the presentation of the data is formatted in the form of a narrative containing the data during the research process. In collecting data, the researcher used observation, interview, and documentation techniques which were then analyzed using three stages, namely data reduction, data presentation, and verification, following the guidelines of qualitative research methodology. Based on the data obtained that the implementation of activities at SMP Negeri 1 Sumberasih can be classified according to the time of implementation into two parts. The first is daily activities which include reading the Koran together, praying in congregation, praying dhuha. Second, weekly activities, which include; Read Surah Yasin onFriday Taqwa.